INFLUENCE OF MONETARY POLICY INSTRUMENTS AND INDICATORS ON DYNAMICS OF FINANCING INNOVATION: EMPIRICAL EVIDENCE - Anargul Belgibayeva; Anastasiia Samoilikova; Tetiana Vasylieva; Serhiy Lieonov (Фінансово-кредитна діяльність: проблеми теорії та практики)
Today innovations are drivers of countries’ economic growth, competitiveness, security, and sustainable development. Financial policy and its instruments play a significant role in innovation management, and monetary instruments are one of the most important components of financial policy. Therefore, the necessity of increasing the efficiency of financial support for innovation development actualizes the study of the impact of the monetary policy instruments and indicators on the level of financing innovation. The aim of the article is to improve the scientific basis for the study of the impact of monetary policy instruments and indicators on the dynamics of financing innovation based on empirical evidence. Information basis of the research was formed from the data for Ukraine and 12 post-soviet and other countries with similar starting economic conditions for 2010-2019, taking into account the availability of statistics from the International Monetary Fund, the World Bank, and the central banks for the whole investigated indicators at the time of the study. The software base included Excel and STATA. The methods of regression (linear regression model with panel-corrected standard errors) and correlation analysis (calculating Pearson and Spearman coefficients) were applied to identify a relationship between monetary instruments and indicators and indicator of financing innovation, confirm the hypothesis about the impact of the monetary instruments and indicators on the financing innovation and formalize this effect. To strengthen the country’s innovation development, it is proved the expediency of lowering the discount rate and real interest rate, increasing “broad money” on general reserves, and increasing liquid reserves on bank assets, as well as the transition to inflation targeting. According to the calculations, for all monetary instruments and indicators, except the discount rate, the directions of influence in Ukraine and the panel from 12 other countries were opposite. This one confirms that monetary instruments in Ukraine are not fully performing their regulatory function, in the context of stimulating innovation development.